Effect of Warm Citronella Compress on Decreasing Osteoarthritis Pain Intensity - Istianah Istianah; Herman Herman; Hapipah Hapipah (Universitas STRADA Indonesia, 2021)
Osteoarthritis is a degeneration disease of the joints involving cartilage, lining of joints, ligaments, and bones causing pain and stiffness in the joints. Non-pharmacological pain management can use warm citronella compresses to reduce pain. This study aims to find out the effect of Warm Citronella Compress on The Decrease in Pain Intensity of Osteoarthritis in The Elderly. This type of research is pre-experimental research with the design of one group pre-post design tests. Observations were made before the intervention and after the intervention with a sample number of 16 people. The analysis used paired T-Test. The results of the data analysis obtained p value = 0.000 which means there is a significant effect in the provision of citronella warm compresses to decrease the intensity of osteoarthritis pain on elderly. It is expected that from the results of this research, citronella can used as a non-pharmacological treatment to reduce the pain.